Spiritualitas Remaja Kristen Masa Kini Dalam Menyikapi Pergaulan Bebas - Jacobs, Jovanca Desvita; Sahertian, Novita L (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Abstract: christian education is education that teaches about the divinity of God in a form of teaching that is given systematically and continuously in order to teach everyone by instilling good attitudes, positive values which can build the right character through teaching. Christian education is very influential the positive thing for young people is, from Christian education young people will get a sense of comfort and calm, they will be taught many things so they can be closer to God. Christian education is very useful in educating the character of young people to be better. Spirituality is a broad concept with various dimensions and perspectives marked by a feeling of attachment (connection) to something bigger than ourselves, which is accompanied by an effort to find meaning in life or can be explained as a universal and touching experience. Some individuals describe spirituality in their life experiences as a feeling of connection/transcendental which is holy and reassuring. Free association can affect a person's personality, which can be in the form of positive or negative influences. Most people think that promiscuity leads to negative things in fashion, trends, and behavior Key Word: Spirituality, Today’s Youth Promiscuity.